2013
DOI: 10.1038/jhg.2013.91
|View full text |Cite
|
Sign up to set email alerts
|

Novel PKD1 and PKD2 mutations in Taiwanese patients with autosomal dominant polycystic kidney disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a heterogeneous disease caused by mutations in PKD1 and PKD2. The genotype-phenotype correlations are not completely understood. We performed direct PCR-sequencing plus multiplex ligation-dependent probe amplification for PKD1 and PKD2 in 46 unrelated patients. Disease-causing mutations were identified in 30 (65%) patients: 23 (77%) patients have mutations in PKD1 and 7 (23%) have mutations in PKD2. Nonsense, splicing or frame-shifting mutations were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…The mutation detection rate (90.0%) in our study (83.3% in PKD1 and 16.7% in PKD2 ) was comparable to previous studies using LR-PCR followed by nested PCR and direct sequencing in clinically well-defined large cohorts in Western countries [ 1 , 3 ]. Although the proportion of PKD2 mutations has been reported to be ~23% in Asian populations [ 16 , 17 ], PKD2 mutations accounted for 16.7% of the total mutations in our study subjects, comparable to data from Western countries (15.0%-16.2%) [ 1 , 3 ]. In contrast, a recent population-based study (Olmsted County population study) [ 24 ] and studies in an outpatient clinic setting [ 25 , 26 ] reported a higher PKD2 mutation detection rate than earlier studies, which recruited large families with a history of ERSD.…”
Section: Discussionsupporting
confidence: 83%
“…The mutation detection rate (90.0%) in our study (83.3% in PKD1 and 16.7% in PKD2 ) was comparable to previous studies using LR-PCR followed by nested PCR and direct sequencing in clinically well-defined large cohorts in Western countries [ 1 , 3 ]. Although the proportion of PKD2 mutations has been reported to be ~23% in Asian populations [ 16 , 17 ], PKD2 mutations accounted for 16.7% of the total mutations in our study subjects, comparable to data from Western countries (15.0%-16.2%) [ 1 , 3 ]. In contrast, a recent population-based study (Olmsted County population study) [ 24 ] and studies in an outpatient clinic setting [ 25 , 26 ] reported a higher PKD2 mutation detection rate than earlier studies, which recruited large families with a history of ERSD.…”
Section: Discussionsupporting
confidence: 83%
“…Given the reduced cost of gene sequencing, such as targeted NGS, and the increasing number ADPKD patients whose phenotype is known, bringing PKD mutation types to clinical practice will likely reduce the economic cost of disease and reduce monitoring in patients destined to be symptom free while proactively increasing preventive monitoring for patients at high risk for progressive renal disease. In addition, defining the genetic mutation in ADPKD will better define the appropriate patient population for randomized clinical trials and develop new rationales for treatment using the molecular information obtained from locus and mutation detection810111213141516171819202122232425262728.…”
Section: Discussionmentioning
confidence: 99%
“…The major disadvantage of linkage analysis is that this method cannot be performed without a sufficient number of affected family members or when the proband is suspected of having a de novo mutation [31]. Although various gene-based screening methods are available for ADPKD molecular testing, such as the LRNS method, HRM method, and even next-generation sequencing methods, direct mutation sequencing remains the preferred choice for making a clinical diagnosis of ADPKD disease [12,14,16,32,33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…Using these unique and lengthy amplification products as templates, nested PCR to amplify each individual exon was followed by sequencing [12,13,14]. Although a variety of methods are used to screen PKD1 mutations, such as high-resolution melt analysis [15], DNA high-performance liquid chromatography (DHPLC) [16], direct sequencing of long-range PCR products [17] and next-generation sequencing [18], long-range then nested PCR and sequencing (LRNS) is the predominant method in many laboratories.…”
Section: Introductionmentioning
confidence: 99%